ChemInform Abstract: Diversity‐Oriented Synthesis of Intensively Blue Emissive 3‐Hydroxyisoquinolines by Sequential Ugi Four‐Component Reaction/Reductive Heck Cyclization. Issue 23 (June 2015) - Moni, Lisa; Denissen, Melanie; Valentini, Gianluca; Mueller, Thomas J. J.; Riva, Renata
Abstract A convergent approach to highly functionalized 3‐hydroxyisoquinolines is reported.